Adverse events following immunization to booster dose (precautionary dose) of COVID-19 vaccine among health-care professionals in a tertiary care teaching institute - Kandula Chaitanya; Mary Rohini P; Bhuvaneshwari G; Edavaluru Shravya; Praneeth Reddy O (Asian Journal of Medical Sciences, 2023)
Background: The worldwide coronavirus disease-2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus. The Government of India announced the booster dose for patients aged 18 or older on April 10, 2022. The booster dose effectively prevented and controlled the spread of COVID-19. This booster dose was effective against Omicron variant as well. Aims and Objectives: The aims of this study were to find out the type of adverse events following immunization to booster dose (precautionary dose) and the treatment for the adverse drug reactions developed to booster dose (precautionary dose) of COVID-19 vaccine. Materials and Methods: A prospective study was conducted among 157 health-care professionals over a period of 6 months, in a tertiary care teaching hospital. Subjects were interviewed for any adverse events at the time of vaccination and followed up at 6 months for delayed adverse effects. The data were collected and entered in Microsoft Excel sheet and analyzed using SPSS software. Results: Total 157 number of health-care professionals received Booster dose (Precautionary dose) of COVID-19 vaccine in our study. Among 157 recipients, 146 were administered with Covishield vaccine (Group 1) and 11 recipients were given Covaxin (Group 2). Majority of health-care professionals were in the age group of 31–40 years. In them majority of females than males. Six recipients tested positive for COVID-19 virus with Covishield and three with Covaxin (Adverse events noted were fever, headache, body aches, chills, cough, cold, and swelling at the inj. site). There was a statistically significant difference between these two groups with P=0.01. Conclusion: This study concludes that all the reported adverse events to booster dose of COVID-19 vaccine were non serious and were mild to moderate, which have subsided with treatment. Even though few studies on first and second dose of COVID-19 vaccine have evaluated cardiac manifestations, these findings are not evident in the present study. Hence, long-term follow-up studies are required to understand the safety of these vaccines in multiple age groups and with comorbidities.